PERAN SERTA MASYARAKAT DALAM UPAYA PEMBERANTASAN TINDAK PIDANA NARKOTIKA DITINJAU DARI UNDANG-UNDANG NOMOR 35 TAHUN 2009 (Studi Kasus Wilayah Hukum Kelurahan Kawal Kecamatan Gunung Kijang Kabupaten Bintan) - Siahaan, kennedy; rahmanidar, rahmanidar (PETITA, 2019)
In the current era of globalization, society tends to develop which causes the mindset of the more advanced society. The development of the community also resulted in the community trying to make renewal in all areas of technology. Increasing people's mindset and technological progress have an impact on increasing crime by using sophisticated modus operandi, especially in Narcotics and drugs. Narcotics is the greatest enemy for the next generation of nation not only the responsibility of the Police but also the responsibility of the society itself. Public participation is active means that the public must report when the occurrence of Narcotic criminal acts are very useful in combating illicit traffic Narcotics. The existence of Community Empowerment Agency. Agency can be a container in tackling and preventing the circulation of Narcotics crime in the community.Recognizing that Narcotics Crime is a big Crime and has wide impact for many people, so that in the effort to overcome the Government and Police need support from the public participation in order to eradicate Narcotics crime which is rampant circulating. However, in the implementation there are limitations of the community itself which resulted in the delayed destroyed Narcotics crime.The method or type of research used by the author is the method of empirical normative law research which is a combination of normative legal approach with the addition of some empirical elements. While the data collection method that is done is direct observation to the field to get real and objective data. The type of data used by the authors in this study is, Primary data, supported by secondary data, this data is obtained from literature materials and interviews from several sources.In this chapter the authors describe and explain with reference to the formulation of the problem, the authors can draw conclusions, among others, that community participation in the eradication and control of Narcotics crime is very important. Therefore the need for Government's attention through the Community Empowerment Institute to protect and invite the community who is the front guard pion to fight Narcotics. The obstacles to eradication and control of Narcotics are the lack of infrastructure, the number of personnel from the Institute of Community Empowerment itself and the public knowledge about the dangers of Narcotics.